Physiological and biochemical properties of three cultivars of wax apple (Syzygium samarangense [Blume] Merrill & L.M. Perry) fruits - Mohammad Moneruzzaman, Khandaker; A.B.M. Sharif, Hossain; Nashriyah, Mat (2015)
A study under field condition was carried out to evaluate physiological and biochemical properties of three cultivars of wax apple (Syzygium samarangense) namely ‘Jambu Madu Red’, ‘Masam Manis Pink’ and ‘Giant Green’. Physicochemical parameters, such as stomatal conductance, fruit development, pigmentation, fruit shape, yield, total soluble solids (TSS), titratable acidity (TA), sugar acid ratio, vitamin-C (vit-C), chlorophyll, carotene and anthocyanin content, in three cultivars of wax apple were investigated. The highest stomatal conductance, color development and yield were recorded in ‘Jambu Madu Red’ cultivar. Lowest amount of TA, highest TSS, sugar acid ratio and carotene content were also observed in this cultivar. Earlier color development, fruit maturity, good shape, highest vit-C and anthocyanin content were found in ‘Masam Manis Pink’. Meanwhile, the highest chlorophyll a, b and total chlorophyll (chlab) content and late maturation fruit were recorded in ‘Giant Green’ Cultivar. Stomatal conductance showed positive correlation with yield and fruit biomass. It is concluded that ‘Jambu Madu Red’ and ‘Masam Manis Pink’ cultivars are comparatively better yield than those of ‘Giant Green’ cultivar grown under tropical field conditions.